Canine Traditional Laboratory Tests and Cardiac Biomarkers - Gavazza, Alessandra; Fruganti, Alessandro; Turinelli, Vanessa; Marchegiani, Andrea; Spaterna, Andrea; Tesei, Beniamino; Rossi, Giacomo; Cerquetella, Matteo (Frontiers in Veterinary Science, 2020)
In small animals, cardiac disease evaluation through laboratory tests can be a challenge. This review will present both historical and updated perspectives on the clinical pathology of cardiac diseases in dogs and demonstrate that laboratory tests are useful tools for the management of patients with cardiac diseases.